Sublethal effects and reproductive hormesis of emamectin benzoate on Plutella xylostella - Liu, Kong-Xing; Guo, Yong; Zhang, Can-Xin; Xue, Chao-Bin (Frontiers in Physiology, 2022)
The diamondback moth (DBM), Plutella xylostella L., is an important pest of cruciferous vegetables, and population control mainly depends on chemical pesticides. Emamectin benzoate is a highly effective insecticide used for controlling DBM. However, it is unknown if low dose residues of emamectin benzoate have sublethal effects on DBM. So the sublethal effects of emamectin benzoate on adult DBM and their progeny were investigated in this study. The pupal weight, pupal period, female fecundity, and vitellin content of the F0 DBM generation increased significantly compared to the control. The pupation rate, adult longevity and ovariole length of the treatment groups decreased significantly. The fecundity of DBM in the treatment groups increased, and this increased the population by a presumptive 13.84%. Treatment also led to the shortening of ovarioles and the reduction of egg hatching, and increased pupal weight in the F1 generation. We concluded that the effects of sublethal/low concentration emamectin benzoate on the different life stages of DBM were variable, and the reproductive hormesis on DBM adults were attractive findings.